2022
DOI: 10.3390/cancers14071617
|View full text |Cite
|
Sign up to set email alerts
|

Role of Adjuvant Radiotherapy in Non-Small Cell Lung Cancer—A Review

Abstract: Background: For patients with completely resected non-small cell lung cancer (NSCLC) with ipsilateral mediastinal lymph node involvement (pN2), the administration of adjuvant chemotherapy is the standard of care. The role of postoperative radiation therapy (PORT) is controversial. Methods: We describe the current literature focusing on the role of PORT in completely resected NSCLC patients with pN2 involvement and reflect on its role in current guidelines. Results: Based on the results of the recent Lung ART a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 82 publications
(143 reference statements)
0
5
0
Order By: Relevance
“…After the end of concurrent chemoradiotherapy, PD-L1 inhibitors can also be used for immunoconsolidation therapy. [61,64,65] Systemic treatment for stage IV lung cancer is the main means, advanced patients should receive genetic testing, targeted therapy is better than chemotherapy. Patients who do not have the gene mutation may choose immunotherapy and/or chemotherapy.…”
Section: The Role Of Immunotherapy In the Clinical Treatment Of Lung ...mentioning
confidence: 99%
“…After the end of concurrent chemoradiotherapy, PD-L1 inhibitors can also be used for immunoconsolidation therapy. [61,64,65] Systemic treatment for stage IV lung cancer is the main means, advanced patients should receive genetic testing, targeted therapy is better than chemotherapy. Patients who do not have the gene mutation may choose immunotherapy and/or chemotherapy.…”
Section: The Role Of Immunotherapy In the Clinical Treatment Of Lung ...mentioning
confidence: 99%
“…Moreover, if patients are to undergo an additional adjuvant treatment, the risk for radiotherapy-related pneumonitis can increase. More recent radiotherapy techniques such as, 3D conformal radiation therapy (3D-CRT), IMRT or volumetric modulated arc therapy (VMAT) showed potential benefits while reducing the risks of radiotherapy-related toxicities [35][36][37][38] .…”
Section: Safety Issuesmentioning
confidence: 99%
“…PORT in stage IIIA-N2 NSCLC is a treatment approach that raises concerns regarding the occurrence of toxicities, particularly cardiopulmonary toxicity. Studies have shown that excessive radiation volumes, suboptimal radiation techniques, large doses and fraction sizes, and noncomputed tomography (CT)-based treatment planning contribute to increased toxicity and noncancer-related deaths associated with PORT [20].…”
Section: Port Toxicitymentioning
confidence: 99%